Synthesis and biological activity of methylated derivatives of the Pseudomonas metabolites HHQ, HQNO and PQS - Thierbach, Sven; Wienhold, Max; Fetzner, Susanne; Hennecke, Ulrich (Beilstein Journal of Organic Chemistry, 2019)
Selectively methylated analogues of naturally occurring 2-heptyl-4(1H)-quinolones, which are alkaloids common within the Rutaceae family and moreover are associated with quorum sensing and virulence of the human pathogen Pseudomonas aeruginosa, have been prepared. While the synthesis by direct methylation was successful for 3-unsubstituted 2-heptyl-4(1H)-quinolones, methylated derivatives of the Pseudomonas quinolone signal (PQS) were synthesized from 3-iodinated quinolones by methylation and iodine–metal exchange/oxidation. The two N- and O-methylated derivatives of the PQS showed strong quorum sensing activity comparable to that of PQS itself. Staphylococcus aureus, another pathogenic bacterium often co-occurring with P. aeruginosa especially in the lung of cystic fibrosis patients, was inhibited in planktonic growth and cellular respiration by the 4-O-methylated derivatives of HQNO and HHQ, respectively.
Keywords: antibiotic acitivity; methylation; Pseudomonas aeruginosa; quinolones; quorum sensing